Recombinant long-acting glycoPEGylated factor IX in hemophilia B: A multinational randomized phase 3 trial - Peter W. Collins (2018)
© 2014 by The American Society of Hematology. This multinational, randomized, single-blind trial investigated the safety and efficacy of nonacog beta pegol, a recombinant glycoPEGylated factor IX (FIX) with extended half-life, in 74 previously treated patients with hemophilia B (FIX activity ≤2 IU/dL). Patients received prophylaxis for 52 weeks, randomized to either 10 IU/kg or 40 IU/kg once weekly or to on-demand treatment of 28 weeks. No patients developed inhibitors, and no safety concerns were identified. Three hundred forty-five bleeding episodeswere treated,with an estimated success rate of 92.2%. The median annualized bleeding rates (ABRs) were 1.04 in the 40 IU/kg prophylaxis group, 2.93 in the 10 IU/kg prophylaxis group, and 15.58 in the on-demand treatment group. In the 40 IU/kg group, 10 (66.7%) of 15 patients experienced no bleeding episodes into target joints compared with 1 (7.7%) of 13 patients in the 10 IU/kg group. Health-related quality of life (HR-QoL) assessed with the EuroQoL-5 Dimensions visual analog scale score improved from a median of 75 to 90 in the 40 IU/kg prophylaxis group. Nonacog beta pegol was well tolerated and efficacious for the treatment of bleeding episodes and was associatedwith low ABRs in patients receiving prophylaxis.Once-weekly prophylaxiswith 40 IU/kg resolved target joint bleeds in 66.7% of the affected patients and improved HR-QoL. This trial was registered at www.clinicaltrials.gov as #NCT01333111.